Tumor Microenvironment-Responsive Nanomaterials as Targeted Delivery Carriers for Photodynamic Anticancer Therapy - Liu, Houhe; Yao, Jiwen; Guo, Huanhuan; Cai, Xiaowen; Jiang, Yuan; Lin, Mei; Jiang, Xuejun; Leung, Wingnang; Xu, Chuanshan (Frontiers in Chemistry, 2020)
ABSTRACT: Photodynamic therapy (PDT), as an alternative approach to treat tumors through reactive oxygen species (ROS) produced by the activated photosensitizers (PS) upon light irradiation, has attracted wide attention in recent years due to its mini-invasive and high efficient features. However, the low hydrophilicity and poor targeting of PS limit the clinical application of PDT. Stimuli-responsive nanomaterials represent a major class of remarkable functional nanocarriers for drug delivery. In particular, tumor microenvironment-responsive nanomaterials (TMRNs) can respond to the special pathological microenvironment in tumor tissues to release the loaded drugs, that endows them to control the release of PS within tumor tissues. Recent studies have demonstrated that TMRNs can achieve the targeted release of PS at tumor site, increase the concentration of PS in tumor tissues and reduce side effects of PDT. Hence, in the present paper, we review TMRNs, mainly including pH-, redox-, enzymes- and hypoxia-responsive smart nanomaterials, and focus on the application of these smart nanomaterials as targeted delivery carriers of PS in photodynamic anticancer therapy, to further boost the development of PDT in tumor therapy.